Computational screening of transition-metal single atom doped C9N4 monolayers as efficient electrocatalysts for water splitting. Issue 39 (26th September 2019) - Zhou, Yanan; Gao, Guoping; Kang, Jun; Chu, Wei; Wang, Lin-Wang
Abstract : Ni@C9 N4 performs as a promising bifunctional electrocatalyst with N and Ni atoms as the catalytic active sites for HER and OER, with calculated hydrogen adsorption Gibbs free energy (Δ G H* ) of −0.04 eV and OER overpotential ( η OER ) of 0.31 V. Abstract : The search for high efficiency and low-cost catalysts for the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) is vital to overall water splitting. In this work, on the basis of first-principles calculations, we screened a series of late transition metal atoms supported on a C9 N4 monolayer (TM@C9 N4, where TM represents Mn, Fe, Co, Ni, Cu, Ru, Rh, Pd, Ir, and Pt) as electrocatalysts for both the HER and OER. Our results demonstrate that the TM atoms can be bonded with the nitrogen atoms around the hole to form stable structures, and the bonded TM atoms are stable against diffusion. Co@C9 N4 exhibits high catalytic activity toward the HER. In particular, the N active sites in the Co@C9 N4, Ni@C9 N4, and Pt@C9 N4 systems demonstrate relatively high performance for the HER. However, Co@C9 N4 and Pt@C9 N4 exhibit low OER activities with large overpotentials. Among the ten cases of TM@C9 N4 considered here, only Ni@C9 N4 performs as a promising bifunctional electrocatalyst with N and Ni atoms as catalytic active sites for the HER and OER, with a calculated hydrogen adsorption Gibbs free energy (Δ G H* ) of −0.04 eV and an OER overpotential ( η OER ) of 0.31 V. The results demonstrate that TM@C9 N4 is a promising single-atom catalytic system, which can be used as the non-noble metal bifunctional electrocatalyst for overall water splitting.